In Vitro Inhibition of Rhizoctonia oryzae-sativae Using Bacterial Strains as a Sustainable Alternative for Controlling Sheath Blight in Rice - Liz Cheril Quiñones-Pezo; Winston Franz Ríos-Ruiz; Danny Fran Pompa-Vásquez; Franz Rios-Reategui; Angel David Hernández-Amasifuen; Mike Anderson Corazón-Guivin (International Journal of Plant Biology)
The control of ‘sheath blight’ in rice (Oryza sativa L.), which is caused by the fungus Rhizoctonia oryzae-sativae, has become problematic due to the excessive application of fungicides and their consequent harmful effects. Hence, the search for less contaminating alternatives to conventional chemical products is necessary. This study evaluated the in vitro inhibitory activity of four bacterial strains on the growth of R. oryzae-sativae in both tryptone soy broth (TSB) and mineral medium (MM). The results demonstrated that all evaluated strains (Bacillus tequilensis SMNCT17-02, Priestia aryabhattai SMNCH17-07, Burkholderia vietnamiensis TUR04-01, and Burkholderia vietnamiensis TUR04-03) inhibited the growth of R. oryzae-sativae. Specifically, the activity of B. tequilensis SMNCT17-02 resulted in the smallest area of R. oryzae-sativae growth in both TSB medium (8.54 cm2) and MM (5.53 cm2), suggesting a notable antifungal effect. When evaluating the action of supernatants generated by the growth of the four bacterial strains in TSB and MM culture media, significant inhibition of R. oryzae-sativae growth was only observed for supernatants produced in MM. This inhibition was attributed to the presence of soluble secondary metabolites. These results offer new perspectives in biotechnology, suggesting the possibility of developing effective products based on easily extractable soluble secondary metabolites, thus promoting sustainable agriculture.